2014
DOI: 10.3109/14767058.2014.921675
|View full text |Cite
|
Sign up to set email alerts
|

Number and size of uterine fibroids and obstetric outcomes

Abstract: Women with uterine fibroids are at an increased risk of obstetric complications. In particular, multiple rather than large fibroids are associated with a significantly increased risk of preterm birth and cesarean delivery while large fibroids are associated with a higher risk of pPROM. No correlation with IUGR, placenta previa or placental abruption was found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
89
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(98 citation statements)
references
References 20 publications
4
89
1
4
Order By: Relevance
“…Moreover, uterine fibroids seem to be related to infertility, early pregnancy loss, and several adverse obstetric outcomes. [2,3] The choice of the appropriate therapy for uterine fibroids is influenced by several factors, including the severity of symptoms, infertility, the tumor characteristics (number, size, and location), the patient's age, wish to preserve the uterus, and the desire of future pregnancies. [4] …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, uterine fibroids seem to be related to infertility, early pregnancy loss, and several adverse obstetric outcomes. [2,3] The choice of the appropriate therapy for uterine fibroids is influenced by several factors, including the severity of symptoms, infertility, the tumor characteristics (number, size, and location), the patient's age, wish to preserve the uterus, and the desire of future pregnancies. [4] …”
Section: Introductionmentioning
confidence: 99%
“…Bleeding in first trimester is seen if the placenta implants close to the fibroid, and the incidence of preterm labour, if not preterm premature rupture of membranes, is also increased. Ciavattini et al [10] demonstrated that the risk of preterm labour is significantly increased with both multiple fibroids (29.4% vs 5% in women with no fibroids) as well as with large fibroids >5cm (16.4% vs 5%) [10]. Shavell [5] also demonstrated the earlier mean gestational age of delivery in pregnancies complicated by >5cm fibroids against subgroups of smaller fibroids (1-5cm) and no fibroids (36.5 vs 38.4 vs 36.5 weeks) [5].…”
Section: Discussionmentioning
confidence: 99%
“…Large, multiple fibroids as well as lower segment fibroids increase chances of malpresentations (OR:2.9) and hence caesarean sections (OR:3.7)(10). Multiple fibroids in pregnancy increase caesarean section (73.5% vs 37%, p<0.01) and breech presentation rates (11.8% vs 2.7%, p=0.04) [10]. Blood loss at delivery is increased more so for larger>5cm fibroids than smaller fibroids and normal pregnancy (645ml vs 535ml vs 486ml) [5].…”
Section: Discussionmentioning
confidence: 99%
“…En nuestro estudio, los hallazgos ecográficos sospechosos fueron descritos de forma precoz, en el segundo trimestre de gestación: dos casos en la semana 16 otro en la semana 18 y otro en la 20. La implantación de la placenta sobre el mioma pudo ser factor decisivo (12) aunque no todos los autores encuentran asociación entre útero miomatoso y desprendimiento placentario (13). Concluimos que las imágenes de engrosamiento difuso placentario en ausencia de infección o aneuploidía, combinado con RCIU y oligoamnios podrían predecir la muerte perinatal.…”
Section: Discussionunclassified